Development of Education Games Map Material as a Learning Media for Elementary School Students (Universitas Negeri Semarang, 2018)
The purpose of this study is to describe the development needs and characteristics of education games learning media based on the perceptions of teachers and students, compile and validate education games learning media and test the effectiveness of learning education learning media at Public Elementary School Jatibarang Lor 02. The type of research used is research and development. These stages of research and development include potential problems, product manufacturing, product validation, product revisions, and product trials. Based on the results of the needs analysis, it can be concluded that the development of learning education learning media is in accordance with the characteristics of teachers and students including material aspects, presentation aspects, linguistic aspects, and graphic aspects. These characteristics are developed into education games learning media products that are ready for expert validation testing. Based on the validation test, education games learning media got a score of 84 with good categories. After going through expert validation tests, then the learning media is tested on students. The results showed that education games learning media were effective and could improve cognitive learning outcomes and skills of students at Public Elementary School Jatibarang Lor 02. So, it can be concluded that this education games learning media became one of the solutions in learning elementary school students, especially on map material.